Mitochondrial targeting sequence variants of the CHCHD2 gene are a risk for Lewy body disorders. (8th December 2015) - Ogaki, Kotaro; Koga, Shunsuke; Heckman, Michael G.; Fiesel, Fabienne C.; Ando, Maya; Labbé, Catherine; Lorenzo-Betancor, Oswaldo; Moussaud-Lamodière, Elisabeth L.; Soto-Ortolaza, Alexandra I.; Walton, Ronald L.; Strongosky, Audrey J.; Uitti, Ryan J.; et al.
Abstract : Objective: To assess the role of CHCHD2 variants in patients with Parkinson disease (PD) and Lewy body disease (LBD) in Caucasian populations. Methods: All exons of the CHCHD2 gene were sequenced in a US Caucasian patient-control series (878 PD, 610 LBD, and 717 controls). Subsequently, exons 1 and 2 were sequenced in an Irish series (355 PD and 365 controls) and a Polish series (394 PD and 350 controls). Immunohistochemistry and immunofluorescence studies were performed on pathologic LBD cases with rare CHCHD2 variants. Results: We identified 9 rare exonic variants of unknown significance. These variants were more frequent in the combined group of PD and LBD patients compared to controls (0.6% vs 0.1%, p = 0.013). In addition, the presence of any rare variant was more common in patients with LBD (2.5% vs 1.0%, p = 0.050) compared to controls. Eight of these 9 variants were located within the gene's mitochondrial targeting sequence. Conclusions: Although the role of variants of the CHCHD2 gene in PD and LBD remains to be further elucidated, the rare variants in the mitochondrial targeting sequence may be a risk factor for Lewy body disorders, which may link CHCHD2 to other genetic forms of parkinsonism with mitochondrial dysfunction.